We know that the binomial coefficient (nk) defined by (nk)=n!k!(n−k)!
The Pascal's Identity
For any two positive integers with k≤n, we see that (nk−1)+(nk)=(n+1k)
Let us take the Left-hand Side (L.H.S.) expression and derive the Right-hand Side (R.H.S.) expression.L.H.S=n!(k−1)!(n−(k−1))!+n!k!(n−k)!=n!×kk!(n−k+1)!+n!×(n−k+1)k!(n−k+1)!=n!k!(n−k+1)!(k+n−k+1)=n!(n+1)k!(n+1−k)!=(n+1)!k!((n+1)−k)!=(n+1k)=R.H.S
The following diagram illustrates how the Fibonacci numbers are related to Pascal Triangle:
We know that kth row in Pascal's triangle has k+1 elements and are nothing but the binomial coefficients (k0), (k1), (k2), …, (kk−1), and (kk).
Let us consider the sum of the elements of Pascal Triangle across the arrows and denote nth sum by Pn. We see that P1=(00)=1P2=(10)=1P3=(20)+(11)=1+1=2P4=(30)+(21)=1+2=3P5=(40)+(31)+(22)=1+3+1=5P6=(50)+(41)+(32)=1+4+3=8P7=(60)+(51)+(42)+(33)=1+5+6+1=13P8=(70)+(61)+(52)+(43)=1+6+10+1=18
From this definition, we can derive the Pascal's Identity as shown below:
The Pascal's Identity
For any two positive integers with k≤n, we see that (nk−1)+(nk)=(n+1k)
Proof:
Let us take the Left-hand Side (L.H.S.) expression and derive the Right-hand Side (R.H.S.) expression.L.H.S=n!(k−1)!(n−(k−1))!+n!k!(n−k)!=n!×kk!(n−k+1)!+n!×(n−k+1)k!(n−k+1)!=n!k!(n−k+1)!(k+n−k+1)=n!(n+1)k!(n+1−k)!=(n+1)!k!((n+1)−k)!=(n+1k)=R.H.S
The following diagram illustrates how the Fibonacci numbers are related to Pascal Triangle:
Relationship of Fibonacci Numbers to Pascal Triangle |
Let us consider the sum of the elements of Pascal Triangle across the arrows and denote nth sum by Pn. We see that P1=(00)=1P2=(10)=1P3=(20)+(11)=1+1=2P4=(30)+(21)=1+2=3P5=(40)+(31)+(22)=1+3+1=5P6=(50)+(41)+(32)=1+4+3=8P7=(60)+(51)+(42)+(33)=1+5+6+1=13P8=(70)+(61)+(52)+(43)=1+6+10+1=18
From the above illustration, we can observe that Pn+1=⌊n2⌋∑k=0(n−kk),∀n≥0.
By Pascal's Identity, ((n+1)−kk)=(n−kk)+(n−kk−1)
Thus, we see that
Pn+2=⌊n+12⌋∑k=0((n+1)−kk)=(n+10)+⌊n+12⌋∑k=1((n+1)−kk)=1+⌊n+12⌋∑k=1(n−kk)+⌊n+12⌋∑k=1(n−kk−1)=(n−00)+⌊n+12⌋∑k=1(n−kk)+⌊n+12⌋−1∑k=0(n−(k+1)k)=⌊n+12⌋∑k=0(n−kk)+⌊n+12⌋−1∑k=0((n−1)−kk)
Case 1: n is even
If n is even, then n+1 is odd, and hence ⌊n+12⌋=⌊n2⌋=n2.
Pn+2=⌊n+12⌋∑k=0(n−kk)+⌊n+12⌋−1∑k=0((n−1)−kk)=⌊n2⌋∑k=0(n−kk)+⌊n−12⌋∑k=0((n−1)−kk)=Pn+1+Pn
If n is odd, then both n−1 and n+1 are even. Hence, we observe that ⌊n+12⌋−1=n+12−1=n−12=⌊n−12⌋=⌊n2⌋.
Now, we consider two possible cases for n.
Case 1: n is even
If n is even, then n+1 is odd, and hence ⌊n+12⌋=⌊n2⌋=n2.
Also, note that n−1 is odd, and hence ⌊n+12⌋−1=n2−1=n−22=⌊n−12⌋.
Thus,
Pn+2=⌊n+12⌋∑k=0(n−kk)+⌊n+12⌋−1∑k=0((n−1)−kk)=⌊n2⌋∑k=0(n−kk)+⌊n−12⌋∑k=0((n−1)−kk)=Pn+1+Pn
Case 2: n is odd.
If n is odd, then both n−1 and n+1 are even. Hence, we observe that ⌊n+12⌋−1=n+12−1=n−12=⌊n−12⌋=⌊n2⌋.
Thus,
Pn+2=⌊n+12⌋∑k=0(n−kk)+⌊n+12⌋−1∑k=0((n−1)−kk)=⌊n2⌋+1∑k=0(n−kk)+⌊n−12⌋∑k=0((n−1)−kk)=⌊n2⌋∑k=0(n−kk)+(n−n+12n+12)+Pk=Pn+1+0+Pn=Pn+1+Pn.
From the above discussion, we can see that P1=1P2=1Pn+2=Pn+1+Pn,∀n≥1
This is exactly the same as the recursive definition of the Fibonacci Numbers: F1=1F2=1Fn+2=Fn+1+Fn,∀n≥1.
Thus, we can assert that the Fibonacci Numbers associated with Pascal Triangle as shown in the above diagram.